Comparative efficacy of wet wipe preservatives: antimicrobial performance to inhibit microbial growth - Hakim, M. Arif Lukman; Permadi, Adi; Astuti, Erna; Mohamed, Farahidah (Department of Sciences Education. Faculty of Teacher Training and Education Mataram University, Indonesia, 2025)
The global market for wet wipes has seen significant growth in the past decade, establishing them as a popular product for personal care and household use. However, their high water and cellulose content makes them vulnerable to contamination by pathogenic microorganisms, which can cause changes in both their physical and chemical properties. This study aims to evaluate the efficacy of six preservative formulations in preventing microbial contamination in wet wipes. The formulas tested included: Formula 1 (F1) with phenoxyethanol and benzalkonium chloride; Formula 2 (F2) with phenoxyethanol, sodium benzoate, and potassium sorbate; Formula 3 (F3) with phenoxyethanol and caprylyl glycol; Formula 4 (F4) with polyaminopropyl biguanide and caprylyl glycol; Formula 5 (F5) with sodium benzoate, potassium sorbate, and cetylpyridinium chloride; and Formula 6 (F6) with propylene glycol and chlorphenesin. A 28-day challenge test was conducted using a multispecies inoculation technique, including bacteria, mould, and yeast. All formulas were initially sterile, as confirmed by sterility testing. The results showed that Formula F1 was the most effective, reducing microbial growth by over 6 log units within 14 days. Formulas F5 and F6 also demonstrated effectiveness, though microbial reduction in these formulas was slower, only reaching >6 log reduction by day 28. Formulas F2, F3, and F4 did not meet the required standards for mould and yeast reduction. These findings support the use of Formula F1 as the most reliable preservative combination, ensuring the safety and quality of wet wipes.